The usefulness and feasibility of the physical education school programme in the opinions of teachers from selected schools in the province Silesia and Opole - Dariusz Pośpiech; Justyna Blacha (Health Promotion & Physical Activity, 2018)
Introduction: One of the objectives of the core curriculum reform was to diversify school physical education and to adapt it to the interests of students. Nowadays, there is an alarming decline in physical activity among young people, both in school and non-school classes, and the school offers to choose a favorite sport discipline lose with out-of-school offers. Searching for effective solutions was a necessity. Methods: The research was conducted in 2013 among 74 junior high and high school teachers. The method of a diagnostic survey using a questionnaire was used. The arithmetic mean of the results was calculated. A chi-square goodness of fit test (x^2) was performed to determine the significance of differences. Results: In most cases, the assessments of men and women were very similar. The data show that the highest ratings of suitability and feasibility were obtained by the thematic blocks: "Sports of all life and leisure" and "Sport". For many years, sports games have been the most desirable content of physical education lessons by students and, as shown by the results of the conducted research, also physical education teachers. Conclusions: The obtained results indicates that physical education teachers positively assess the content of the core curriculum implemented in 2009. The surveyed teachers assessed the usefulness of the core curriculum content much better than its feasibility.